2019
DOI: 10.1093/ofid/ofz280
|View full text |Cite
|
Sign up to set email alerts
|

Routine Immediate Eye Examination at the Point of Care for Diagnosis of AIDS-Related Cytomegalovirus Retinitis Among Patients With a CD4 Count <100 in Myanmar

Abstract: A retrospective review of diagnosis of cytomegalovirus retinitis (CMVR) before and after introduction of routine immediate eye examination among AIDS patients in Myanmar with an absolute CD4 T-cell count <100 cells/μL demonstrated an increased detection of CMVR from 1.1% (14/1233) to 10.7% (65/608), an improvement of ~10-fold. Diagnosis of CMVR was achieved a mean of 2 days after clinic enrollment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Such observations again support the need for universal screening for all patients with a CD4 < 100 cells/ μL [1,4]. After the inception of the CMVR programme in our clinic, the detection rate of CMVR among patients with CD4 < 100 cells/μL was 10.7% [16].…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Such observations again support the need for universal screening for all patients with a CD4 < 100 cells/ μL [1,4]. After the inception of the CMVR programme in our clinic, the detection rate of CMVR among patients with CD4 < 100 cells/μL was 10.7% [16].…”
Section: Discussionsupporting
confidence: 75%
“…IOG injections are invasive, are traumatic for patients and care providers, and are associated with possible complications including blindness. Although we and others have shown that HIV clinicians can be trained to safely perform IOG injections, this has not been scaled up [9,10,15,16]. In many countries, only ophthalmologists are sanctioned to perform intraocular injections [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the early diagnosis of both HIV and CMV infection is particularly important. CD4+ T lymphocyte counts have been used to predict the onset of several ocular infections in HIV-positive persons (Douek et al, 2009); for example, studies have shown that patients with HIV infection with CD4 + T lymphocyte counts below 100 cells/µL often have retinal or conjunctival microangiopathy as well as CMV retinitis (Ei et al, 2019). Moreover, 30% of PLHIVs with CD4 + T lymphocyte counts below 50 cells/µL have CMV retinitis with blindness mainly due to posterior retinal detachment in these persons (Holbrook et al, 2003).…”
Section: Introductionmentioning
confidence: 99%